Enhancement of graphene biocompatibility as a potential nano-carrier for drug delivery applications using natural deep eutectic solvent / Mohamad Hamdi Zainal Abidin - Mohamad Hamdi , Zainal Abidin (2020)
Graphene has attracted massive interest in numerous biomedical applications such as anti-cancer therapy, drug delivery, bio-imaging and gene delivery. Therefore, it is important to ensure that graphene is nontoxic, and that its cellular biological behavior is safe and biocompatible. Herein, a new route was used to enhance the biocompatibility of graphene as a nano-carrier for potential drug delivery applications, using different compositions of natural deep eutectic solvents (DESs) as functionalizing agents, owing to their capability to introduce various functional groups and surface modifications. To meet this end, eight different combinations of binary and ternary DESs were synthesized using choline chloride salt with several hydrogen bond donors (i.e., urea, glucose, fructose, sucrose, glycerol and malonic acid). Characterizations of the physicochemical changes in DES-functionalized graphene were conducted by FE-SEM, EDX, FTIR, XRD, BET and Raman spectroscopy. The cytotoxicity profile of DES-functionalized graphenes on human breast adenocarcinoma (MCF-7), human gastric adenocarcinoma (AGS) and macrophage cell line (RAW264.7) was significantly improved compared to pristine graphene and oxidized graphene, as demonstrated by cell viability, cell cycle progression, and reactive oxygen species evaluation assays. This work also studied the association between cellular toxicity of DES-functionalized graphene and their physicochemical properties. The application of DESs as functionalizing agents, especially for DES choline chloride (ChCl):malonic acid (1:1), ChCl:glucose:water (5:2:5) and ChCl:glycerol:water (1:2:1), significantly reduced the cytotoxicity level of graphenes. Next, it was selected doxorubicin and tamoxifen, as representatives of common anti-cancer drugs, to load on the DES-functional graphene samples. Subsequently, the drug loading capacity and entrapment efficiency were determined. The DES ChCl:malonic acid (1:1) and ChCl:glucose:water (5:2:5) functionalized graphenes demonstrated higher tamoxifen and doxorubicin entrapment efficiency and loading capacity in comparison to the other DES-functionalized graphenes. The drug-loaded on the DES-functionalized graphene possessed higher toxicity level against MCF-7 and AGS cell lines in comparison to unloaded graphenes. The drug-loaded DES-functionalized graphene also had destructive effects against cancerous cells through the generation of intracellular ROS and cell cycle disruption phenomena. The anti-cancer activity of drug-loaded graphene was confirmed by real-time cell growth analysis. Across all tested cellular kinetic models, the most significant reduction in the growth rate constant of cancerous cells was obtained using graphene functionalized with DES ChCl:glucose:water (5:2:5) and ChCl:fructose:water (5:2:5). Overall, DES-functionalized graphene demonstrated improved anti-cancer activity compared to non-functionalized graphene. This study supports DESs as potential green functionalizing agents for nano drug carriers, owing to their lower cytotoxicity, higher drug loading capacity and better anti-cancer activity.